Performance assessment of a new variable stiffness probing system for micro-CMMs - Alblahaihid, Khalid; Kinnell, Peter; Lawes, Simon; Desgaches, Dorian; Leach, Richard K. (MDPI, 2016)
When designing micro-scale tactile probes, a design trade-off must be made between the stiffness and flexibility of the probing element. The probe must be flexible enough to ensure sensitive parts are not damaged during contact, but it must be stiff enough to overcome attractive surface forces, ensure it is not excessively fragile, easily damaged or sensitive to inertial loads. To address the need for a probing element that is both flexible and stiff, a novel micro-scale tactile probe has been designed and tested that makes use of an active suspension structure. The suspension structure is used to modulate the probe stiffness as required to ensure optimal stiffness conditions for each phase of the measurement process. In this paper, a novel control system is presented that monitors and controls stiffness, allowing two probe stiffness values (“stiff” and “flexible”) to be defined and switched between. During switching, the stylus tip undergoes a displacement of approximately 18 _m, however, the control system is able ensure a consistent flexible mode tip deflection to within 12 nm in the vertical axis. The overall uncertainty for three-dimensional displacement measurements using the probing system is estimated to be 58 nm, which demonstrates the potential of this innovative variable stiffness micro-scale probe system.